Effect of the Application Time of Paecilomyces spp. on t he Pressure of Root - Knot Nematodes ( Meloidogyne spp.) on Tomato ( Lycopersicum esculentum Mill.) - Winarto Winarto; Reflinaldon Reflinaldon (Jurnal Proteksi Tanaman)
The application time of Paecilomyces spp. was assumed affecting its ability to suppress the root knot nematode (Meloidogyne spp.). This study aimed to get the effective application time to suppress Meloidogyne spp. The study was carried out at greenhouse and Biological Control Laboratory of Faculty of Agriculture, University of Andalas from March to June 2015. The research method used was compeletely random design (CRD) with 5 treatments and 4 replications. The application times consisted of 14 days before planting, 7 days before planting, at planting time, 7 days after planting, 14 days after planting and control. Application time of Paecilomyces spp. on 7 days before planting was the best time to reduce the number of root knot, the group of nematode eggs, nematode eggs and nematode larvae in the soil.